(untitled) (The Pakistan Development Review, 2015)
Since the emergence of known civilisation poverty is a major challenge and in the present era, it is a wide spread world problem specifically afflicting the developing countries and also is a breeding ground for terrorism and conflicts between nations [Shirazi and Khan (2009)]. Poverty problem, with issues, of defining poverty, determining who is poor and where to draw the poverty line has been at the forefront of national and international policy-making forums, and a topic of heated debates among economists and policy makers [Khan (2007)]. Increasing per capita income along with equal distribution of wealth leading to better standard of life (with better facilities and opportunities of: food, health, clothing, housing, drinking water, income and employment, and social and cultural life) is pertinent way to reduce poverty. Islam encourages with stress on working hard and investment for earning the livelihood. For extremely poor who have no means to meet basic needs, no sources to invest, and no opportunity to earn, Islam suggested voluntary and compulsory endowments [Zakat, waqf, sadqa] for catering the needs of different degrees of poor from destitute to less poor, and also causing, circulation of wealth leading to it equal distribution, which is also another way to reduce poverty.